2003
DOI: 10.1139/y02-168
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy influence on the vascular interactions between nitric oxide and other endothelium-derived mediators in rat kidney

Abstract: Peripheral vascular resistance and sensitivity to circulating pressor and vasoconstrictor agents are blunted during pregnancy. This has been mainly attributed to an increased production of endothelium-derived mediators. The objective of this work was to evaluate if pregnancy changes the relative participation of nitric oxide (NO) and prostaglandins (PG) in respect to the modulation of the increases in renal perfusion pressure induced by phenylephrine (Phe). Dose-response curves were made with gradually increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…This differs from the finding in pregnant dogs, wherein LV eNOS protein expression was increased at 60 days gestation (23). Many other studies have shown upregulation of eNOS in aorta and resistance arteries during pregnancy but often a downregulation in organs like the kidney (3,4,24). Therefore, our findings are consistent with published literature.…”
Section: Discussionsupporting
confidence: 74%
“…This differs from the finding in pregnant dogs, wherein LV eNOS protein expression was increased at 60 days gestation (23). Many other studies have shown upregulation of eNOS in aorta and resistance arteries during pregnancy but often a downregulation in organs like the kidney (3,4,24). Therefore, our findings are consistent with published literature.…”
Section: Discussionsupporting
confidence: 74%
“…Pregnancy-associated vasodilatation has been attributed, in part, to hormones such as prostaglandins [3], nitric oxide (NO) [3], [4], [5], endothelium-derived hyperpolarizing factor [6], and more recently, relaxin, which is considered an important regulator of renal and cardiovascular function during pregnancy [7], [8]. The serum levels of relaxin increase soon after conception in humans and near day 8 of gestation in rats [9].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, these adaptations are followed by an 80 and 50% rise in the renal plasma flow (RPF) and glomerular filtration rate (GFR), respectively [ 1 ]. Relaxin, estrogen, prostaglandins and nitric oxide (NO) modulate these adaptations [ 2 5 ]. Pregnancy also imposes a necessary expansion of the extracellular volume (ECV) by sodium and water retention via mechanisms involving changes in the expression of tubular transporters.…”
Section: Introductionmentioning
confidence: 99%